Hacia unas bases teóricas de la educación ambiental - González Gaudiano, E.; Alba Ceballos, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
This essay intends to provide theoretical tools to analyze and formulate environmental education projects. The article works on theory concept, contrasting different intelectual traditions: positivism, interpretative and critical, in order to illustrate its function in the explanation of reality. It calls to develop an own environmental education theory in Latin America and the Caribbean, and suggests some analytical guidelines for projects.